VD_FINDINFO Décision / 2016 / 32 vom 11. November 2015 - VD Tribunal cantonal (2015)
CONTRAVENTION, CALCUL DU DÉLAI, DÉCISION D'IRRECEVABILITÉ, JUGE UNIQUE | 398 al. 4 CPP (CH), 399 al. 1 CPP (CH), 403 al. 1 let. a CPP (CH), 403 al. 3 CPP (CH), 406 al. 1 let. c CPP (CH), 14 al. 3 LVCPP